La relación entre el Reino de Marruecos y el Estado de Israel: una cooperación geopolítica pragmática de larga trayectoria - Gil Fons, Antonio (El Colegio de México A.C., 2023)
The establishment of official diplomatic relations between the State of Israel and the Kingdom of Morocco in December 2020 is undoubtedly a significant event. However, it must be seen as a step forward within the context of wide-ranging pragmatic geopolitical cooperation between Tel Aviv and Rabat since the middle of the twentieth century. Considering this perspective, this article presents an analysis using the neoclassical realism approach to relations between Israelis and Moroccans, which have made the North African country one of the most notable actors in Israel’s peripheral strategy to strengthen its national security.